A novel two-stage optimization method for beam–plate structure design. (November 2016) - Li, Kai; Wang, Yunlong; Lin, Yan; Xu, Wei; Liu, Manting
In this article, a novel optimization method for beam–plate structure is proposed based on two optimization levels, including the topology optimization and the section optimization. First, the optimal topology of structure with fixed material and dimensions of design domain is obtained using bidirectional evolutionary structure optimization method, and then, the section optimization is made to produce final optimal solution based on response surface model. In order to deal with beam–plate structures, the traditional bidirectional evolutionary structure optimization method is improved using cubic box as the unit cell instead of solid unit to construct periodic lattice structure. To handle irregular structural element layout produced in bidirectional evolutionary structure optimization method, section conversion process is employed to smooth the edges of sections; in this way, the manufacturability of optimal solution will be significantly improved. To determine the section parameters, response surface method is used to perform the section optimization, and the structure mass is further reduced. One example of cantilever beam structure design is provided and discussed. The applied two-stage optimization procedure resulted in 86 iteration steps to obtain the optimal topology, and a further decrease in 2.65% mass on the basis of optimal topology, which shows that the proposed method has advantages on convergence rate and computational cost.